My PHD formula P + H + D PHD / Julenah Ag Nuddin - Ag Nuddin, Julenah (Universiti Teknologi MARA, Sabah, 2021)
The highest formal academic qualification is the degree of Doctor of Philosophy. Currently, in US alone, 1.77% of its population has doctorates or its equivalent degree holders. It differs in every country depending on the quality of education system that it has. As it is the highest recognition for academic performance, a lot have dreamt to hold the revered scroll. However, quite a number have failed trying. There are a lot of descriptions for the acronym PhD; the most frightening one, Permanent Head Damage. Upon reflection, one description fits well. The formula of success for obtaining PhD consists of the elements known as strategical Plan (P), the rich health (H) and the awesome determination (D). This paper is elaborating these three elements and more, required for a person who is attempting to acquire the degree based on a review of literature and my personal experiences. Hopefully, it will be able to help those who are still fighting their way through their journey.